Importance of Information in Crisis Management – Statistical Analysis - Simeunović, Ivana; Vukajlović, Vladimir; Beraha, Isidora; Brzaković, Miodrag (Industrija, 2019)
The article reports on a statistical analysis of the importance and role information plays in crisis management. The purpose of the research is to empirically examine the impact that information makes on crisis management and on activities conducted by crisis managers. The empirical research is conducted using the questionnaire approach. Questionnaire was designed to capture the most relevant aspects of crisis management as perceived by respondents with an aim to examine how information affects crisis management and which organizational factors affect the information flow in crisis. The research sample included 299 respondents from the wider are of the City of Belgrade. The data were analyzed using the SPSS Software Package. The research results indicate that appropriate methodology enables organizations to manage crisis and better avoid its consequences, as well as that quality of crisis managers, professional staff, informing process, internal and external communication, timely sharing and information accuracy in crisis, as well as knowledge and capabilities of employees and managers to use information have average to high impact on the quality of crisis management.
Keywords: statistical analysis; Crisis management; Information